Volunteerism is a vehicle for sustainable development - Nur Husnina; Asmuni, Azizan; Ismail, Ismi Arif (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
Youth are human capital used by a nation for a long term investment. Youth play important role in shaping the future of politics, economy and society in Malaysia. Volunteers devoted to their life to help others regardless their time and effort. However, in 2010, the numbers of volunteers dropped significantly. It is important to study what predictors that contribute intention to volunteers among youth. Volunteering is the course of action that individual’s willing to perform without anticipating any payment to help other people, community and organization. A vast literature was conducted using through various database such as Emerald, Goggle Scholar, Science Direct, Psychological and Behavioral Science Collection and reference list from key studies used to locate information relevant to the study. Articles were used to define volunteerism, and development theoretical model for predictors in volunteerism among youth. Continued studies of predictors of volunteering behavior can promote participation in volunteering activities.